Demographic and economic inequality of antenatal care coverage in 4 African countries with a high maternal mortality rate - Winini Belay; Amanuel Belay; Tariku Mengesha; Mizan Habtemichael (BMC, 2024)
Abstract Background Maternal deaths are concentrated in low and middle-income countries, and Africa accounts for over 50% of the deaths. Women from socioeconomically disadvantaged households have higher morbidity and mortality rates and lower access to maternal health services. Understanding and addressing these inequalities is crucial for achieving the Sustainable Development Goals and improving maternal health outcomes. This study examines the demographic and economic disparities in the utilization of antenatal care (ANC) in four countries with high maternal mortality rates in Africa, namely Nigeria, Chad, Liberia, and Sierra Leone. Method The study utilised data from Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys (MICS) from Nigeria, Chad, Liberia, and Sierra Leone. The data was obtained from the Health Equity Assessment Toolkit (HEAT) database. The study examined ANC service utilisation inequality in four dimensions such as economic status, education, place of residence, and subnational region across different subgroups by using four summary measures (Difference (D), Absolute Concentration Index (ACI), Population Attributable Risk (PAR), and Population Attributable Factor (PAF)). Result A varying level of inequality in ANC coverage across multiple survey years was observed in Nigeria, Chad, Liberia, and Sierra Leone. Different regions and countries exhibit varying levels of inequality. Disparities were prominent based on educational attainment and place of residence. Higher level of inequality was generally observed among individuals with higher education and those residing in urban areas. Inequality in ANC coverage was also observed by economic status, subnational region, and other factors in Nigeria, Chad, Liberia, and Sierra Leone. ANC coverage is generally higher among the richest quintile subgroup, indicating inequality. Nigeria and Chad show the highest levels of inequality in ANC coverage across multiple measures. Sierra Leone displays some variation with higher coverage among the poorest quintile subgroup. Conclusion and recommendation Inequalities in ANC coverage exist across age groups and survey years in Nigeria, Chad, Liberia, and Sierra Leone. Disparities are prominent based on education, residence, and economic status. Efforts should focus on improving access for vulnerable groups, enhancing education and awareness, strengthening healthcare infrastructure, and addressing economic disparities.